THE IMPORTANCE OF A HEALTHY MOUTH IN HUMAN HEALTH - Sodikova Shoira Amriddinova; Kholmurodov Jahangir; Ziyadullayev Khondamir; Abdumurodov Nurbek (Scholar Express Journals, 2022)
This article talks about the importance of a healthy mouth in human health. The importance of healthy teeth and gums cannot be overestimated. They play an important role in the formation of speech - they serve as walls, near which the teeth, cheeks and tongue, moving, form sounds, so the condition of the teeth affects the purity of human speech.
Keywords: Healthy mouth; human health; digestive system; dental diseases